Acidogenic fermentation of brewer’s spent grain towards polyhydroxyalkanoates production - Guarda, Eliana da Costa (2020)
Polyhydroxyalkanoates (PHA) are fully biodegradable polyesters, synthesized by microorganisms from renewable resources, which reveal an alternative to petroleum-based plastics. Its production by mixed microbial cultures, unlike pure cultures, allows the use of industrial by-products in the absence of sterility conditions, potentially reducing process costs. The study described focused on the valorization of a waste from a brewery industry, brewer’s spent grain (BSG), through organic acids production, towards PHA production. PHA production using mixed microbial cultures involves three steps: (1) acidogenic fermentation of BSG for organic acids production, (2) selection of the mixed cultures able to accumulate PHA and (3) PHA production. In order to extract the sugars necessary to produce organic acids (phase 1), pre-treatment methods such as acid hydrolysis and subcritical water have been studied. Acid hydrolysis was selected for further experiments as the hydrolysis yield on sugars reached was higher than using subcritical water (0.152 g total sugars g BSG-1 versus 0.008 and 0.020 g total sugars g BSG-1 at 200 °C and 230 °C, respectively). Afterwards, the pH (5.0, 5.5 and 6.0) and organic loads (10, 20 and 30 gCOD L-1) effect on the acidogenic fermentation of hydrolyzed BSG was studied in batch. It was verified, regardless of the condition, that the most produced acids are acetic and butyric. As pH and organic load affects the fermentation products profile, it is possible to manipulate PHA composition. At last, the acidogenic fermentation of hydrolyzed BSG was studied in a continuous mode, using an expanded granular sludge bed reactor (EGSB). Due to the reduced operating time, it was not possible to reach stability. However, it was observed that sugars were consumed to produce organic acids. This revealed the potential of EGSB to be used for BSG acidogenic fermentation towards PHA production.